Etiology and clinical features of Han Chinese patients with Duane retraction syndrome - Huang, Lijuan; Chen, Baoying; Cai, Chi; Wu, Yuyu; Sun, Zhimin; Xie, Yan; Li, Ningdong (Frontiers in Genetics, 2025)
Duane retraction syndrome (DRS) is a congenital ocular motility disorder. The aim of this study was to retrospectively describe the etiology, clinical findings, imaging characteristics, and surgical outcomes of 42 Han Chinese patients with DRS. All patients underwent detailed clinical evaluation. Next-generation sequencing was performed to identify pathogenic variants in the disease-causing genes. Magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) tractography were used to evaluate the patient’s cranial nerves. Surgical procedures were designed individually to correct strabismus, abnormal facial turns, and overshooting. A total of 17 patients were diagnosed with DRS1, 4 with DRS2 and 21 with DRS3. Genetic testing revealed that two novel pathogenic variants of c.377T>C (p. Ile126Thr) and c.659A>G (p. Glu220Gly) in the CHN1 gene and a de novo pathogenic variant of c.1432-2A>T in the SALL4 gene were detected in patients with DRS1. In 12 of the 14 patients with DRS1 and 9 of the 17 patients with DRS3, the abducens nerve was found to be absent in the MRI images, and in 4 of the patients with DRS2, the abducens nerve was detected as hypoplasia. In addition, the projective fibers from the abducens neurons to the contralateral ocular motor neurons via the medial longitudinal fasciculus were also absent in those patients without abducens nerve in DTI images. Thirty-five patients who underwent strabismus surgery gained binocular vision and an improved appearance. In summary, our genetic findings contribute to expanding the spectrum of variants in the CHN1 and SALL4 genes. Molecular etiology and imaging studies support that cranial maldevelopment is a major cause of DRS. Individualized treatment based on ocular movement can effectively improve the symptoms and signs of patients with DRS.